Inter-country Distancing, Globalization and the Coronavirus Pandemic - Klaus F. Zimmermann; Gokhan Karabulut; Mehmet Huseyin Bilgin; Asli Cansin Doker (Global Labor Organization (GLO), 2020)
Originating in China, the Coronavirus has reached the world at different speeds and levels of strength. This paper provides some initial understanding of some driving factors and their consequences. Since transmission requires people, the human factor behind globalization is essential. Globalization, a major force behind global wellbeing and equality, is highly associated with this factor. The analysis investigates the impact globalization has on the speed of initial transmission to a country and on the size of initial infections in the context of other driving factors. Our cross-country analysis finds that measures of globalization are positively related to the spread of the virus, both in speed and size. However, the study also finds that globalized countries are better equipped to keep fatality rates low. The conclusion is not to reduce globalization to avoid pandemics, but to better monitor the human factor at the outbreak and to mobilize collaboration forces to curtail diseases.
Keywords: C30; F69; I19; 330; Globalization; Coronavirus; COVID-19; Pandemic; Inter-country Distancing